Caregiver role strain in caring for vulnerable persons living with HIV: correlates of caregiver and care recipient reports. Issue 10 (3rd October 2022) - Mitchell, Mary; Hansen, Eric; Tseng, Tuo-Yen; Shen, Mary; Catanzarite, Zachary; Cruz-Oliver, Dulce; Parker, Lauren; Knowlton, Amy
ABSTRACT: Informal care of family and friends is important for the health and well-being of disadvantaged persons living with HIV (PLWH). Caregiver role strain may threaten the function and continuity of their main relationships and their health impacts. Data were from a disadvantaged, primarily African American, sample of PLWH care recipients. Caregiver role strain was operationalized as a latent factor measured by variables including PLWH's perceptions of their caregiver not wanting or complaining about helping them or wanting a break. We found that greater caregiver role strain was associated with higher levels of HIV-related stigma and depressive symptoms. Lower role strain was associated with more collaborative problem solving and shared medical treatment decision-making. Caregiver role strain was linked to disadvantaged PLWHs' worse stigma and mental health; collaborative engagement in care and coping assistance were protective of role strain. Caregiving relationship-focused research and interventions are needed for resourcing and sustaining disadvantaged African American communities' caregiving and health.